A comparative kinetics study of CO2 absorption into aqueous DEEA/MEA and DMEA/MEA blended solutions. Issue 4 (22nd November 2017) - Jiang, Wusan; Luo, Xiao; Gao, Hongxia; Liang, Zhiwu; Liu, Bin; Tontiwachwuthikul, Paitoon; Hu, Xiayi
Abstract : The kinetics of CO2 absorption into aqueous solutions of N, N‐diethylethanolamine (DEEA), and N, N‐dimethylethanolamine (DMEA), and their blends with monoethanolamine (MEA) have been studied in a stopped‐flow apparatus. The kinetics experiments were carried out at the concentrations of DEEA and DMEA varying from 0.075 to 0.175 kmol/m 3, respectively, and that of MEA ranging between 0.0075 and 0.0175 kmol/m 3, over the temperature range of 293–313 K. Two kinetics models are proposed to interpret the reaction in the blended amine systems and the results show that the model which incorporates the base‐catalyzed hydration mechanism and termolecular mechanism resulted in a better prediction. Furthermore, the kinetics behaviors of CO2 absorption into two blended systems are comprehensively discussed according to their molecular structures. It can be concluded that the interaction between tertiary amines and primary amines as well as the alkyl chain length of tertiary amines have a significant influence on the kinetics. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1350–1358, 2018